Limits in laparoscopic partial splenectomy in children - Tomuschat, Christian; Aftzoglou, Michail; Hagens, Johanna; Boettcher, Michael; Reinshagen, Konrad (Children, 2022)
The aim of this paper is to assess the effectiveness and perioperative complications of splenic surgeries in children. In 41 splenectomies, an anterior abdominal laparoscopic approach was used, with 35 including a partial laparoscopic splenectomy. Of these, three needed a conversion to open. Six patients had a total splenectomy, three of which were open. Patients ranged in age from 5 to 18 years. Splenectomy was performed for a variety of causes, including hereditary spherocytosis (n = 20), splenic cysts (n = 13), sickle cell disease (n = 3), primary malignancy (n = 1), sepsis (n = 1), embolism (n = 1), anemia (n = 1), and hypersplenism (n = 1). The average length of stay was 7.6 days, and the average operation time was 169.3 min. Pleural effusion in the left hemithorax was found in 31.6% of the patients, with 5.3% requiring a thorax drain. The majority of patients had the highest platelet count two weeks after surgery. There was no evidence of wound infection, pancreatic leak, colon perforation, or postoperative sepsis. The most encountered perioperative complication was bleeding with the need of transfusion (n = 6), and one patient needed a diaphragm repair. A partial splenectomy (PS) can be a difficult procedure with a steep learning curve. For most children who require a splenic operation, this should be the primary procedure of choice.
Dieser Artikel gehört zum Special issue: Current development of pediatric minimally invasive surgery
Gesehen am 11.03.2024